Structural origins for selectivity and specificity in an engineered bacterial repressor-inducer pair - Klieber, Michael A.; Scholz, Oliver; Lochner, Susanne; Gmeiner, Peter; Hillen, Wolfgang; Muller, Yves (Febs Journal, 2009)
The bacterial tetracycline transcription regulation system mediated by the tetracycline repressor (TetR) is widely used to study gene expression in prokaryotes and eukaryotes. To study multiple genes in parallel, a triple mutant TetR(KLI) has been engineered that is selectively induced by the synthetic tetracycline derivative 4-de-dimethylamino-anhydrotetracycline (4-ddma-atc) and no longer by tetracycline, the inducer of wild-type TetR. In the present study, we report the crystal structure of TetR(KLI) in the absence and in complex with 4-ddma-atc at resolutions of 2.1 Å. Analysis of the structures in light of the available binding data and previously reported TetR complexes allows for a dissection of the origins of selectivity and specificity. In all crystal structures solved to date, the ligand-binding position, as well as the positioning of the residues lining the binding site, is extremely well conserved, irrespective of the chemical nature of the ligand. Selective recognition of 4-ddma-atc is achieved through fine-tuned hydrogen-bonding constraints introduced by the His64→Lys substitution, as well as a combination of hydrophobic effect and the removal of unfavorable electrostatic interactions through the introduction of Leu135 and Ile138. © 2009 FEBS.